Land Service Quality in Public Sector: A Bibliometric Analysis - Seran, Gotfridus Goris; Salbiah, Euis; Pratidina, Ginung; Wahyudin, Cecep (Indonesian Journal of Social Research (IJSR), 2025)
Few studies employed bibliometric analysis to examine land service quality in the public sector. Using bibliometric analysis, this research focused on identifying the topics studied, mapping the trend of studies, and presenting future research. This research extracted data from the Google Scholar database through Publish or Perish based on the keyword "land service quality". Data from this research were collected during April 2025 and yielded 992 articles published during 2020-2024. Data processing employed VOSviewer overlay visualization to map keywords and clusters of topics, the trend of topics, and the latest topics for future research regarding land service quality in the public sector. This research revealed that the most dominant topics focused more on environmental and spatial aspects than social, institutional, or administrative aspects of land service governance. This research also indicated the trend of research topics shifting from purely environmental issues to an integrative approach with aspects of land degradation, food security, arable land, evidence, and comprehensive review (data-based approaches). In addition, this research delineated studies emphasizing the land issues over the services as the core tasks of the public sector (the government). However, institutional governance, policies, public service systems, participation, and fairness of community access to land resources mainly influenced future research. This research was still limited by extracting data only from the Google Scholar database. Moreover, this research contributed as a valuable reference and literature for other researchers who have used bibliometric analysis to study the topic of land service quality in the public sector.